Recent Decadal Trend in the North Atlantic Wind Energy Resources - Chong Wei Zheng; Chong Yin Li; Xin Li (Advances in Meteorology)
This study presents the climatic trend of the North Atlantic wind energy using cross-calibrated, multiplatform (CCMP) wind data for the period 1988–2011. Results show the following. (1) The North Atlantic WPD exhibited a significant increasing trend of 4.45  (W/m2)/yr over the past 24 years. (2) The variation in the North Atlantic Ocean WPD shows a noticeable regional difference. More than half of the North Atlantic Ocean has a significantly increasing trend in WPD. The increasing trend in the mid-high latitudes is stronger than that in the low latitudes, and the trend is stronger in the west than in the east. The area with the strongest increasing trend is located along the southern coast of Greenland of 35 (W/m2)/yr. (3) There is a noticeable seasonal difference in the variation of WPD. The strongest increasing trend occurs in December-January-February (DJF), followed by September-October-November (SON) and March-April-May (MAM), and the weakest occurs in June-July-August (JJA). The increasing trend in different areas is dominated by different seasons. (4) There is no leading or lagging correlation between WPD and the North Atlantic Oscillation (NAO). However, there is a noticeable negative correlation between the Niño3 index and WPD in most of the North Atlantic.